THE STUDY OF COLOR-DENOTING UNITS IN LINGUISTICS - Masharipova Umidakhon Khudayberganovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the developmental stages, theoretical foundations, and primary scientific approaches to the study of color-denoting units (coloratives) in global and Russian linguistics. It highlights the lexical-semantic, typological, ethnolinguistic, cognitive, and linguacultural aspects of color lexicon, describing the interconnectedness of color terms with human cognition, cultural experience, and the language system based on scientific sources. Furthermore, the paper synthesizes research on the semantic structure, metaphorical and symbolic meanings, and functional characteristics of color-denoting units within phraseology and literary texts. The study concludes that investigating color lexicon through a comprehensive approach allows for a deeper understanding of its role within the conceptual and linguacultural systems of language.